Вплив телебачення як засобу масової комунікації на формування цільової аудиторії - Недбальська, Мар’яна; Марковець, Олександр (Видавництво Львівської політехніки, 2012)
This article is devoted to study the influence of TV on the target audience. In particular, the theoretical approaches to study the phenomenon of the influence of television, the concept of efficiency of media exposure, the nature and specific channels and mechanisms for its effective impact.
Keywords: ЗМІ; цільова аудиторія; телебачення; коментування репортажів